The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1123/pes.21.4.384
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Assessed by Accelerometry in Rural African School-Age Children and Adolescents

Abstract: Physical activity (PA) in children/adolescents of both genders from a rural community in Mozambique was estimated by accelerometry and by questionnaire and was compared with PA of Portuguese youth. Total PA, moderate (MPA), vigorous (VPA) and very vigorous (VVPA) were evaluated. Mozambican boys were more active than girls. Intensity of PA declined significantly with age. Survival activities, such as household tasks, were the predominant mode of PA. Compared with Portuguese children/adolescents, Mozambicans had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 26 publications
8
35
2
1
Order By: Relevance
“…Female gender and older age brackets showed higher rates of inactivity. Studies in different regions of Brazil 18,21,25,26 and in other countries 13,32,33,34 agree with these findings. Importantly, however, there are studies indicating no association between these two variables and physical activity in adolescents 17,35 .…”
Section: Discussionsupporting
confidence: 67%
“…Female gender and older age brackets showed higher rates of inactivity. Studies in different regions of Brazil 18,21,25,26 and in other countries 13,32,33,34 agree with these findings. Importantly, however, there are studies indicating no association between these two variables and physical activity in adolescents 17,35 .…”
Section: Discussionsupporting
confidence: 67%
“…[24][25][26][27][28][29] Obesity prevention interventions should not exclude physical activity as an option because of concerns over the possible existence of an 'Activitystat'. On the contrary, recent evidence on the importance of environmental influences on objectively measured habitual physical activity of children, positive systematic reviews on the efficacy of interventions and continuing improvements in intervention science, all argue for greater efforts to promote physical activity in future obesity prevention interventions.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Comparisons of groups living modern lifestyles (in urban and rural North America) versus those living more traditional lifestyles (for example, from old order Amish and Mennonite communities in North America) report consistently that more traditional lifestyles are characterised by much higher levels of objectively measured physical activity. These observations emphasise the importance of the environment as a determinant of physical activity in children and adolescents, and the great flexibility of child and adolescent habitual physical activity across different environments.…”
Section: Genetic Versus Environmental Influence On Habitual Physical mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review of worldwide variation in PA levels of adolescents from 105 countries, Hallal et al 10 reported that more than 80% of youth do not achieve the recommended daily MVPA levels; further, this prevalence tended to be lower Portugal and Mozambique are countries with different social, economic and cultural characteristics. A previous study conducted in 2009 comparing PA levels in 6-to 16-year-old school-age children and adolescents from these two countries 15 reported that rural Mozambican youth engaged in significantly higher PA levels than their Portuguese peers. However, due the urbanization process that has affected the lifestyles of youth from these two countries, this scenario could not be seen in a more recent study 16,17 .…”
Section: Introductionmentioning
confidence: 96%